Prarancangan Pabrik Gliserol Dari Epiklorohidrin Dan Natrium Hidroksida Kapasitas 50.000 Ton/Tahun - Luthfiany, Ananda; , Rois Fatoni, S.T., M.Sc, Ph.D sel (2017)
Glycerol is chemical product that have many used as medical treatment, food ingredients, and cosmetics in chemical industry. Glycerol plant had established for fulfill the chemical product needed and the other purpose is to export. Glycerol plant from epichlorohydrin and NaOH that has capacity of 50.000 ton/year will operated in 330 days/year. Glycerol is reacted in Continuous Stirred Tank Reactor. In this case, reaction happened in liquid-liquid phase, irreversi C and pressure of 5 atm. NaOH as raw material is diluted with water from utility as NaOH solution in 2 mixer, then entered to reactor and epichlorohydrin from its tank. After out from reactor, product is neutralized with HCl in neutralizer and then evaporated in evaporator to condense the product. Amount of NaCl as bottom side product will filtrated in settler and the glycerol liquid as top side product will entered the flash drum to separate fast. The product includes glycerol of 6313,13 kg/hour and NaCl of kg/hour.Support utilities includes supplying product water extracted from Bengawan Solo river of kg/hour. Supplying saturated steam og kg/hour from boiler with fuel oil. Supplying pressure air of kg/hour. Supplying electricity from PLN and generator of 750 kW. This plant will established in Gresik with land area of 45.000m2 and total number of employees are 139 people. Glycerol plant that will established requires FCI (Fixed Capital Investment) of Rp 805.321.691.294,81 and working capital of Rp 182.496.011.745,13. From the economic analysis of this plant, pretax profit of Rp 312.502.103.929,86 and after tax 30 % profit reaches Rp 218.751.472.750,90. ROI (Return of Investment) before tax is 38,80 % and after tax is 27,16 %. POT (Pay Out Time) before tax for the year of 2,05 and 2,69 year after tax. BEP (Break Even Point) amounted to 43,06 % and SDP (Shut Down Point) accounted to 26,37 %. Discounted Cash Flow (DCF) accounted for 43,6 %. From the data above feasibility analysis concluded that the plant is profitable and feasible to set